Effect of Chemicals and Cincturing on Quality of Litchi Fruit cv. Bombai - Mandal, D.; Sarkar, A.; Ghosh, B. (International Journal of Economic Plants, 2017)
Indian litchi has got tremendous importance so far the domestic as well as the international markets are concerned because of its appearance, size and quality. In India, West Bengal is the second largest litchi producing state after Bihar where the commercial cultivation is based on single cultivar ‘Bombai’. The present study was performed with an objective to measure the effect of certain chemicals viz. Paclobutrazol (25% w/v) @ 2 ml and 3 ml a.i. m-2 of canopy spread, Ethrel (40%) @1.0 ml and 2.0 ml l-1, KNO3 1.0% and 2.0% along with cincturing (during September and October) against untreated plant on quality fruit production. The plants treated with ethrel @ 2 ml l-1 produced maximum fruit weight (21.94 g), pulp weight (16.17 g) and juice content (62.79ml per100g pulp). The Total Soluble Solids (TSS) and TSS:acid ratio was also found highest 20.15 oBrix and 40.95 under this treatment. However, cincturing during September also enhanced the fruit weight (21.39 g) compared with control (19.57 g).